Microseismic reflection imaging of the Central Andean crust. Issue 2 (6th January 2016) - Schmelzbach, C.; Kummerow, J.; Wigger, P.; Reshetnikov, A.; Salazar, P.; Shapiro, S.A.
Abstract: The coda of passive seismic recordings is often rich in arrivals that are coherent across several stations. If reflections can be extracted, then they may be used for seismic reflection subsurface imaging. With the objective to image the upper crust of the North Chilean Precordillera (Central Andes; approximate location 21°S 69°W), we developed a workflow to process passive seismic data into subsurface reflection images. We analysed the waveform recordings of several hundred microseismic events using signal processing and imaging techniques adapted from active (controlled source) seismic imaging as used in the oil industry. Key processing steps involved precise arrival time picking and hypocentre determination, removing signal amplitude variations due to varying source radiation patterns, identification and separation of reflections from coherent noise, and transformation of the processed waveforms into images of the subsurface reflectivity. When designing our microseismic reflection imaging workflow, we took advantage of the fact that the passive seismic recording geometry with the hypocentres located at depth and the receivers positioned at the surface resembles a reverse vertical-seismic profiling experiment. The resultant P - and S -wave reflection images reveal several reflective features, such as an approximate 15° westward dipping reflector over the 5–25 km depth range that largely coincides with a distinct seismicity boundary. We interpret the imaged interface as the brittle-ductile transition zone boundary, possibly enhanced by a tectonic shear zone. For the area of the North Chilean Precordillera, the deduced microseismic reflection sections with horizontal extensions of about 50 km represent the first high-resolution images of the shallow crust, which could not be obtained from previous active-source seismic-reflection data.